2018
DOI: 10.14419/ijet.v7i2.5.10045
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the impact of perceived organizational support and psychological contract fulfillment of employees paradoxical intentions of stay and leave

Abstract: The article presents a comprehensive and detailed conceptual framework on the effects of employees' perceived organizational support on their paradoxical intentions of leaving to and staying with the organization in Psychological Contract Perspective. This study anticipates proposing an applicable technique to examine empirically the interrelationships of employees' perceived organizational support, psychological contract fulfillment, intention to stay and intention to leave. This paper proposes theory-based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Present study fills this gap by examining the aforesaid relationship in Indian context. Second, the article highlighted the indirect mechanism which explains the relationship between POS and ITS (Akhtar et al, 2018). Study examined the mediating role of EE in developing the employee’s ITS by enhancing POS among employees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present study fills this gap by examining the aforesaid relationship in Indian context. Second, the article highlighted the indirect mechanism which explains the relationship between POS and ITS (Akhtar et al, 2018). Study examined the mediating role of EE in developing the employee’s ITS by enhancing POS among employees.…”
Section: Discussionmentioning
confidence: 99%
“…Though, it has been noticed that despite the direct impact of POS on ITS, this relationship can be explained through indirect mechanism (Akhtar et al, 2018; Liu & Liu, 2016; Naim & Lenka, 2017). However, regardless of growing research interest, the majority of the research on POS has examined direct relationship between POS and business outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These propositions can be tested by adopting or adapting instruments having high validity and reliability. The study of (Akhtar, Salleh, Ghafar, Khurro, and Mehmood, 2018) suggested that these conceptual models empirically can validate and measure these variables and their relationships with the structural equation model which is one of the most reliable techniques to measure the relationship between concepts and to test propositions. The proposed research design has been given in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers made the erroneous assumption that the intention to stay is the inverse of the intention to quit an organization (turnover intention) (Chinomona, 2017;Chinomona & Dhurup, 2015;Dabke & Patole, 2014;Johari et al, 2012;Li, Zhang, Yan, Wen, & Zhang, 2020;Woon, Tan, & Nasurdin, 2017). However, some scholars now disagree and argue that turnover and retention are not "two sides of the same coin" (Akhtar, Salleh, Ghafar, Khurro, & Mehmood, 2018;Cardy & Lengnick-hall, 2011;George, 2015;Holtom, Mitchell, Lee, & Eberly, 2008;Nancarrow et al, 2014). This is because the potential causes of employee turnover can usually explain why employees quit their jobs, but they are unable to explain why employees choose to stay in their employment (Akhtar et al, 2018;Sanjeevkumar, 2012).…”
Section: Intention To Staymentioning
confidence: 99%